If m1 and m2 are the gradients to two perpendicular lines, prove that m1*m2 = -1.How to prove that the product of gradient of two perpendicular lines is equal to -1?
say we have three points:
P1 (0,0)
P2 (x1,y1)
P3 (x2,y2)
line1 goes through P1 and P2
line 2 goes through P1 and P3
m1 = (y1-0)/(x1-0) = y1/x1
m2 = (y2-0)/(x2-0) = y2/x2
define each line as vectors:
vector1 = %26lt;x1,y1%26gt;
vector2 = %26lt;x2,y2%26gt;
these vectors are perpendicular if they're dot product equals zero
x1x2 + y1y2 = 0
x1x2 = -y1y2 rearrange
x1/y1 = -y2/x2
-x1/y1 = y2/x2
substitute into m formulas:
m1 = y1/x1
m2 = y2/x2 we know that y2/x2 = -x1/y1
m2 = -x1/y1
product the two slopes
m1m2 = (y1/x1)(-x1/y1) = -1
voila
Subscribe to:
Post Comments (Atom)
No comments:
Post a Comment